2021
DOI: 10.1111/mila.12379
|View full text |Cite
|
Sign up to set email alerts
|

Missing persons: Young children's talk about absent members of their social network

Abstract: Little is known about young children's ability to talk about absent members of their social network. We analyzed the speech of four children from 2 to 5 years. References to absent caregivers were relatively frequent, even when children were 2 years old. Such references were often generated spontaneously rather than being repetitions of a name produced by the child's interlocutor. Children's comments about absent family members occasionally expressed concern about contact with them but were predominantly neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 67 publications
5
10
0
Order By: Relevance
“…objects, actions, attributes, or locations). Yang et al (2021) found a similar pattern for children’s references to absent persons in American child–parent conversations. Thus, we expected that Mandarin-speaking children would often refer to absent persons spontaneously across development and not simply echo their interlocutor’s references.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…objects, actions, attributes, or locations). Yang et al (2021) found a similar pattern for children’s references to absent persons in American child–parent conversations. Thus, we expected that Mandarin-speaking children would often refer to absent persons spontaneously across development and not simply echo their interlocutor’s references.…”
Section: Introductionmentioning
confidence: 54%
“…When do children produce references to absent persons? Yang et al (2021) reported that English-speaking children mentioned absent persons eight times per hour on average in the initial period of their study (i.e. from 24 to 35 months) and as noted, most of those references were neutral or reflective utterances about the absent person rather than contact-related.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations